In situ construction of polymer-encapsulated Au nanoparticle dimers based on a C–C coupling reaction. Issue 42 (16th May 2017) - Jin, Qi; Zhang, Chenjie; Zhang, Jing; Yuan, Yaxian; Xu, Minmin; Yao, Jianlin
Abstract : A polymer-encapsulated Au nanoparticle dimer was fabricated via C–C coupling reaction. The strong effect of LSPR, SERS and SPR catalysis were observed in the gap. It is expected to provide rich information for understanding SERS mechanism. Abstract : The assembly of simple nanostructures has already attracted significant interest in the field of plasmonic devices and other relevant areas. From the viewpoint of theoretical simulation and practical application, the precise control of nanoparticles still remains a significant challenge. Herein, a strategy was successfully developed to fabricate in situ a polymer-encapsulated Au nanoparticle dimer based on the C–C coupling reaction of p -aminophenylacetylene ( p -APAC). The balance between the polymerization processes and the coupling reaction resulted in Au nanoparticle assemblies with different configurations, such as monomer, dimer, and multimer, depending on the concentration of p -APAC. The gap distance of about 1.8 nm was well consistent with the length of the coupling products of p -APAC, i.e. the gap distance was about double the length of a single p -APAC molecule. The observation of a longitudinal peak in the UV-vis spectrum demonstrated that the aspect ratio of the Au nanoparticles was about 2.5, indicating the formation of Au dimers with reasonable yield. Moreover, the thickness of the polymer shell was well-controlled via changing the concentration of p -APAC. The gap of the dimer resulted in a very large coupling effect of the localized surface plasmon resonance (LSPR), and the surface enhanced Raman spectroscopy (SERS) signal of the molecules was accordingly enhanced in the gap areas, which served as the hot spots. Based on the characteristic spectral feature of the coupling products, the single Au nanoparticle dimer was positioned via SERS mapping. The large LSPR coupling effect in the gap area allowed the conversion of p -nitrothiophenol (PNTP) to dimercaptoazobenzene (DMAB) with high efficiency. Thus, it was confirmed that the SPR-catalyzed coupling reaction preferentially occurred on a hot spot area. The proposed approach is expected to be developed into a promising tool for precisely controlling the gap distance of a nanoparticle assembly, and it may serve as a simple model for theoretical consideration in understanding the SERS mechanism(s).